Magnetically Reconfigurable Unidirectional Propagation of Electromagnetic Waves by Zero-Index–Based Heterostructured Metamaterials - Luo, Qilin; Zhao, Lingzhong; Zhou, Jialin; Zhang, Lin; Wen, Guangfeng; Ba, Qingtao; Wu, Huabing; Lin, Zhifang; Liu, Shiyang (Frontiers in Materials, 2022)
We present a zero-index–based heterostructured magnetic metamaterial (HSMM) composed of two arrays of ferrite rods with different radii and lattice separations, which exhibits unidirectional propagation of electromagnetic (EM) waves, and the unidirectionality is reconfigurable dependent on the bias magnetic field (BMF). By calculating the photonic band diagrams and the effective constitutive parameters, it is shown that, for the MMs with two groups of lattice separations and ferrite rod radii, the effective refractive index is switched either from effective zero index (EZI) to effective positive index (EPI) by decreasing the BMF for one MM or from EZI to effective negative index (ENI) for the other MM by increasing the BMF. As a result, two kinds of HSMMs can be constructed with the combination of either EZI and ENI or EZI and EPI, both of which can be used to implement the unidirectional transport of EM waves and exhibit reconfigurable unidirectionality by either decreasing or increasing the BMF, thus providing us with more degrees of freedom. The concept put forward in the present work can be possibly extended to the heterostructured metamaterials made of phase-change materials and realize reconfigurable EM properties in optical frequency by tuning the temperature.